Simulation and Fabrication of Hybrid Electric Bicycle with Multi Charging Mode - Indhumathi, B.; Mercy, E. Latha (Journal of Electronics and Informatics, 2024)
The use of electric vehicles actively contributes to environmental conservation. Lack of EV charging infrastructure is one of the most common challenges associated with the electric vehicles. The conventional method for the electric propulsion system deals with the single mode of charging techniques. The alternative battery charging techniques helps to enhance the usage of electric vehicles. In this work hybrid electric bicycle is designed with multi charging method. In addition to the conventional wall charger, a solar panel and dynamo is used to charge the battery. Increasing the performance and efficiency by means of BLDC motor. The entire propulsion system is connected with the PI controller which calculate the speed and relevant voltage needed for the drive. The performance of the proposed method is evaluated through simulation using MATLAB/ Simulink software.
Keywords: BLDC Motor; Lead Acid Battery; Dynamo; Solar panel; Accelerator; Sprocket